(untitled) (Journal of NELTA, 2016)
Nursing English in Pakistan is an important domain that comes under the ambit of ESP ‘English for Specific Purposes’. English cogitates as a lingua franca and a cornerstone for success in any field. However, in ESL/ELT it is imperative to design a course that caters to the needs of the learners. Thereby this study attempts to evaluate the existing English for Nursing Purposes curriculum of BScN Programme prescribed by HEC/PNC to corroborate its relevancy and adequacy in preparing the musing professionals for their professional English language requirements using Stufflebeam’s curriculum evaluation framework. This investigative study measures the level of existing linguistic (in)adequacy of the professional nurses pertaining to the specific roles they are required to perform so that their problematical areas could be identified systematically and subsequently reported with recommendations. A qualitative research approach has been used to measure the needs of the nurses. Tools like open-ended questionnaires and semi-structured interviews have been used to collect data from the sample sizes nursing heads and language instructors consecutively. The findings of the study divulge that the course is inadequate and yet relevant. It is recommended to review the English language curriculum considering the needs of the nurses for their work place that may improve the standards of nursing English in Pakistan. Journal of NELTA, Vol 21 No. 1-2, December 2016, page: 1-10